2009
DOI: 10.1088/0264-9381/26/8/085005
|View full text |Cite
|
Sign up to set email alerts
|

Thin-shell wormholes in Einstein–Yang–Mills–Gauss–Bonnet theory

Abstract: A thin-shell Lorentzian wormhole with spherical symmetry has been constructed in Einstein-Yang-Mills-Gauss-Bonnet theory. The generalized Darmois-Israel matching conditions are applied to the bounding shell and energy localized on the shell has been calculated. The amount of exotic matter for the existence of the wormhole has been evaluated and it has been shown graphically for certain choices of the parameters involved that ordinary matter is sufficient for the formation of thin-shell wormholes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Our emphasis is on Einstein's general relativity instead of modified theories such as the Lovelock theory. In such theories there were attempts to find such physical wormholes [37][38][39][40][41][42][43][44] with a non-physical solution and it was shown that a TSW supported by positive energy was possible. In this context we have shown that TSWs with oblate sources can be employed to admit overall physical (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our emphasis is on Einstein's general relativity instead of modified theories such as the Lovelock theory. In such theories there were attempts to find such physical wormholes [37][38][39][40][41][42][43][44] with a non-physical solution and it was shown that a TSW supported by positive energy was possible. In this context we have shown that TSWs with oblate sources can be employed to admit overall physical (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The construction of a thin-shell wormhole (TSW) follows the standard procedure of cutting and pasting [37][38][39][40][41][42][43][44]. We consider two copies of ZVW spacetime and we remove from each…”
Section: Zvw Thin-shell Wormhole (Tsw)mentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with the general relativistic case, the equation of motion for the shell is much more complicated. For this reason, although thin-shell wormholes have been investigated in Einstein-Gauss-Bonnet gravity by many authors [67,[77][78][79][80][81][82][83], the stability analysis has not been completed yet even against radial perturbations.…”
Section: Pure Tension Wormholes In Einstein-gauss-bonnet Gravitymentioning
confidence: 99%
“…Also, the mouths of a wormhole open into two different regions of the same space-time or different two space-times in the presence of an exotic matter called phantom violating the energy conditions [1,2]. However, it has been shown that a wormhole can be formed without an exotic matter; i.e., it can be supported by ordinary matter not violating energy condition [3][4][5][6][7][8][9][10][11][12]. Furthermore, a wormhole space-time is topologically similar to a black hole except for the nature of their horizon.…”
Section: Introductionmentioning
confidence: 99%